Potentials of Mean Force for Acetylcholine Unbinding from the Alpha7 Nicotinic Acetylcholine Receptor Ligand Binding Domain - Zhang, Deqiang (2006)
The nicotinic acetylcholine receptor is a prototype ligand-gated ion channel that mediates signal transduction in the neuromuscular junctions and other cholinergic synapses. The molecular basis for the energetics of ligand binding and unbinding is critical to our understanding of the pharmacology of this class of receptors. Here we used steered molecular dynamics to investigate the unbinding of acetylcholine from the ligand-binding domain of human alpha7 nicotinic acetylcholine receptor along four different predetermined pathways. Pulling forces were found to correlate well with interactions between acetylcholine and residues in the binding site during the unbinding process. From multiple trajectories along these unbinding pathways, we calculated the potentials of mean force for acetylcholine unbinding. Four available methods based on Jarzynski's equality were used and compared for their efficiencies. The most probable pathway was identified to be along a direction approximately parallel to the membrane. The derived binding energy for acetylcholine was in good agreement with that derived from the experimental binding constant for acetylcholine binding protein, but significantly higher than that for the complete human alpha7 nicotinic acetylcholine receptor. In addition, it is likely that several intermediate states exist along the unbinding pathways.